Risk stratifying emergency department patients with acute pulmonary embolism: Does the simplified Pulmonary Embolism Severity Index perform as well as the original?. Issue 148 (December 2016) - Vinson, David R.; Ballard, Dustin W.; Mark, Dustin G.; Huang, Jie; Reed, Mary E.; Rauchwerger, Adina S.; Wang, David H.; Lin, James S.; Kene, Mamata V.; Pleshakov, Tamara S.; Sax, Dana K.; Sax, Jordan M.; et al.
Abstract: Introduction: The Pulmonary Embolism Severity Index (PESI) is a validated prognostic score to estimate the 30-day mortality of emergency department (ED) patients with acute pulmonary embolism (PE). A simplified version (sPESI) was derived but has not been as well studied in the U.S. We sought to validate both indices in a community hospital setting in the U.S. and compare their performance in predicting 30-day all-cause mortality and classification of cases into low-risk and higher-risk categories. Materials and methods: This retrospective cohort study included adults with acute objectively confirmed PE from 1/2013 to 4/2015 across 21 community EDs. We evaluated the misclassification rate of the sPESI compared with the PESI. We assessed accuracy of both indices with regard to 30-day mortality. Results: Among 3006 cases of acute PE, the 30-day all-cause mortality rate was 4.4%. The sPESI performed as well as the PESI in identifying low-risk patients: both had similar sensitivities, negative predictive values, and negative likelihood ratios. The sPESI, however, classified a smaller proportion of patients as low risk than the PESI (27.5% vs. 41.0%), but with similar low-risk mortality rates (< 1%). Compared with the PESI, the sPESI overclassified 443 low-risk patients (14.7%) as higher risk, yet their 30-day mortality was 0.7%. The sPESI underclassified 100 higher-risk patients (3.3%) as low risk who also had a low mortality rate (1.0%). Conclusions: Both indices identified patients with PE who were at low risk for 30-day mortality. The sPESI, however, misclassified a significant number of low-mortality patients as higher risk, which could lead to unnecessary hospitalizations. Highlights: The original and simplified PE Severity Indices accurately identify low-risk patients. Low-risk patients on both indices have 30-day all-cause mortality < 1%. The simplified Index misclassifies 15% of low-mortality patients as higher risk. Misclassification by the simplified Index could lead to unnecessary hospitalization.